Q.5 What should be taken away from\( 3x^2 – 4y^2 + 5xy + 20 \)to obtain \(– x^2 – y^2 + 6xy + 20?\)


Answer :

\( 3x^2 – 4y^2 + 5xy + 20 – m = -x^2 – y^2 + 6xy + 20\)
\( m= 3x^2 – 4y^2 + 5xy + 20 – (-x^2 – y^2 + 6xy + 20) \)
\(m= 3x^2 – 4y^2 + 5xy + 20 + x^2 + y^2 – 6xy – 20 \)
\(m = 3x^2 + x^2 – 4y^2 + y^2 + 5xy – 6xy + 20 – 20 \)
\(m = 4x^2 – 3y^2 – xy \)

NCERT solutions of related questions for Algebraic Expressions

NCERT solutions of related chapters class 7 maths

NCERT solutions of related chapters class 7 science